Half-Metallic Ferromagnetism in CdI2-type MX2 (M = V, Nb; X = Cl, Br, I) Compounds: An Ab-initio Investigation - G. Jaiganesh; G. Kalpana (Recent Developments in Engineering Research Vol. 12, 2021)
The tight-binding linear muffin-tin orbital with the atomic sphere approximation (TB-LMTO-ASA) method was used to investigate the possibility of half-metallic ferromagnetism in CdI2-type MX2 (M = V, Nb; X = Cl, Br, I) compounds. The spin-polarization calculations show that VX2 (X = Cl, Br, I) compounds exhibit half-metallic ferromagnetism with a magnetic moment of 3.0 µB per formula unit as expected at their equilibrium volume. Their half-metallic behavior persists within a small range of volume compression. However, the NbX2 (X = Cl, Br, I) compounds show non-magnetic behavior at their equilibrium volume, whereas these compounds become ferromagnets under large volume expansion. In addition to this, NbX2 (X = Cl, Br, I) compounds exhibit half-metallic property too. The variation of lattice constant with the magnetic moment for VX2 (X = Cl, Br, I) compounds is also analyzed. The magnetism arises mainly from the cation d-like states. The ground-state properties like equilibrium lattice parameters, bulk modulus, the heat of formation, magnetic moments, spin-flip-gap, and minority spin-band-gap are calculated and compared with available results. These materials may be useful in spintronic devices and other applications.